Measuring electrical activity in the brain during exercise: A review of methods, challenges, and opportunities - Bigliassi, M.; Wright, M.; Karageorghis, C.; Nowicky, A. (Sport & Exercise Psychology Review, 2020)
During the last decade, the use of mobile electroencephalography (EEG) devices has furthered understanding of the mechanisms that underlie psychophysical and affective responses during the execution of gross movements (e.g., walking and cycling). Such devices can also be used to shed new light on the mechanisms that underlie attention allocation, fatigue-related symptoms, emotional reactions, and behavioural outcomes to physical activity programmes. This advancement could, potentially, herald a new era for the field of sport and exercise psychology, wherein researchers will be able to investigate athletic performance and exercise behaviour from a different perspective. Objective: In this review, we explore some of the most recent approaches used to measure electrical activity in the brain during exercise. Practical Recommendations: We provide an overview of the practical issues that researchers face in this field, such as dealing with artefacts elicited by body and cable movements and how to process the biological signal. We also review methods that researchers can employ to prevent electrical artefacts from compromising the fidelity of data. We make a case for assessing psychological and psychobiological parameters in tandem with EEG in order to arrive at a fuller understanding of exercise-related phenomena.